Phylogenetic relationships of the north-eastern Atlantic and Mediterranean blenniids - Almada, F. (2005)
The phylogenetic relationships of 27 north-eastern Atlantic and Mediterranean blennioids are analysed based on a total of 1001 bp from a combined fragment of the 12S and 16S mitochondrial rDNA. The most relevant results with implications in current blenniid taxonomy are: (1) Lipophrys pholis and Lipophrys (= Paralipophrys) trigloides are included in a well-supported clade that by the rule of precedence must be named Lipophrys; (2) the sister species of this clade are not the remaining species of the genus Lipophrys but instead a monotypic genus comprising Cory-phoblennius galerita; (3) the smaller species of Lipophrys were recovered in another well-supported and independent clade, which we propose to be recognized as Microlipophrys; (4) although some authors included the genera Salaria and Lipophrys in a single group we have never recovered such a relationship. Instead, Salaria is more closely related to the genera Scartella and Parablennius; (5) the genus Parablennius, which was never recovered as a monophyletic clade, is very diverse and may include several distinct lineages; (6) the relative position of Aidablennius sphynx casts some doubts on the currently recognized relationships between the different blenniid tribes. Meristic, morphological, behavioural and ecological characters support our results and are also discussed. The possible roles of the tropical West African coast and the Mediterranean in the diversification of blenniids are discussed. (c) 2005 The Linnean Society of London.